Improvement of the Solar-Thermal Characteristics of the Flat-Plate Collector Using a Composite Coating - H. Jasim, Ruaa; A. Al-Tabbakh, Ahmed; M. Hasan, Sinan (Al-Nahrain Journal of Science, 2021)
A commercially available matt black paint is used as the primary component of a composite coating for low-temperature flat collector systems. The composite coating is composed of the paint, carbon black powder (CBP) and lithium metal oxide (LMO) powder. The CBP and LMO powders are added on the top of the primary paint to improve the solar-thermal conversion characteristics of the collector. The optical and solar-thermal conversion characteristics of these coatings are investigated by means of optical microscopy, optical spectrophotometry, total reflectance measurement, and the measurement of the maximum collector temperature. Results show that the solar-thermal conversion response (maximum temperature) of the collector plate can be improved with the addition of the CBP and LMO powder at low concentrations. This is been demonstrated and discussed in this report. The coatings prepared in the present work can easily be applied on the collector surface and exhibit competing characteristics to other coatings.